Research progress in authenticity identification and detection technology of honey - ZHANG Yifan; CHEN Qi; CUI Zongyan; ZHNANG Jinjie; SHEN Lirong (浙江大学学报. 农业与生命科学版)
As a kind of natural, nutrient-rich food and health care product, honey is favored by consumers around the world. However, it is a highly adulterated food. Therefore, the research on the authenticity identification and detection technology of honey has been long deeply concerned. Here, domestic and international researches on the honey quality were summarized, and a vision about the identification techniques and authenticity analysis of honey in recent 20 years was introduced. According to the comprehensive analysis, the authenticity of honey could be identified to some extent effectively by modern detection technology which is conducive to the quality control of honey. However, there existed defects such as requiring expensive instruments, complex operation, long testing time, professional background and fixed operating location, etc. Moreover, it is difficult to eliminate honey adulteration completely as the development and application of the existing honey detection technology have fallen behind the adulteration technology. It is necessary to develop specific identification technology mainly focusing on the endogenous honey components, not on the exogenous substances. In recent years, the research and application of biomarkers based on genomics and proteomics are very common in related fields. However, there are no reports on identification of honey authenticity and nectar based on these technologies. It is expected that developing a new fast test technique based on honey characteristic markers—immuno-colloidal gold chromatographic test strips or kits will be the main development direction of honey quality control and authenticity identification technology in the future.